PELATIHAN PEMBUATAN BUKET SNACK SEBAGAI KADO WISUDA DI SMK NEGRI 1 KEDUNGWUNI - Muhammad Faqih Fahriza; Putri Amanda Ardita; Niharotul Faizah; Ria Anisatus Solihah; Hendri Hermawan (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2022)
SMK 1 Kedungwuni is one of the vocational schools in Pekalongan Regency. A bouquet is a beautiful flower as a sign of congratulations or a bouquet of snacks, which is currently trendy, is a series of snacks that are made into a bouquet and are usually handed over at a graduation ceremony or given as a gift. This can be used as a means to explore the creativity of SMK students. For this reason, training activities were made in the context of community service, which aims to increase the creativity of Kedungwuni 1 Vocational High School students. The number of students from SMK 1 Kedungwuni who took part in this training activity were 5 students. Based on the training that has been given, the results show that the students responded very positively to this, with evidence that the participants took part in the training provided actively and took part in making the snack bouquets. After this training was carried out, it was also known that 3 out of 5 of the participants were able to make a snack bouquet or had a very good understanding of it. 1 person understands enough and 1 person does not understand.